Improving Student’s Speaking Ability Through Guessing Game for Ninth Grade of MTs Nurul Islam Kediri - Sa'adah, Siti Lailatus; Ningrum, Ary Setya Budhi; Saharani, Annisa Aulia; Amin, Samah Samir Abd El Ghany (Indonesian Journal of Multidisciplinary Educational Research, 2024)
The aim of this research is to investigate the impelementation of guessing games to improve students’ speaking skills of ninth grade at MTs Nurul Islam Kediri in the 2023/2024 academic year. The research design consists of four stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The research subjects were 29 students in class IX-B MTs Nurul Islam Kediri, consisting of 18 male students and 11 female students. Data collection techniques include observation and tests. The results of this research show that the implementation of Guessing Game can improve students’ speaking skills of IX at MTs Nurul Islam Kediri. This can be seen from the increase in the percentage of student learning activities from 63.2% to 84% and the impact on the average student learning outcomes which increased from 79.31 to 84.62